Effect of Video Triggering During Conventional Lectures on Final Grades of Dental Students in an Oral Biology Course: A Two‐Year Retrospective Study. Issue 12 (1st December 2015) - Farooq, Imran; Al‐Jandan, Badr A.
Abstract : The aim of this study was to analyze the effect of the inclusion of video triggers in conventional face‐to‐face lectures on the final grades of dental students in an oral biology course. The study consisted of two groups of students taking the course in two academic years at a dental school in Saudi Arabia: group 1, 2013–14 (control); and group 2, 2014–15. The total sample comprised 163 students (n=163; group 1: 71 and group 2: 92). Group 1 received lectures without any videos, whereas group 2 received lectures that included two to three videos of one to five minutes in duration with triggering effect (a video was shown every 10–15 minutes into the lecture). The final examination grades of the students were accessed retrospectively, and the data were compared with a chi‐square test. The results confirmed that a higher number of students who received video triggering during lectures (group 2) performed better than their counterparts who did not receive video triggers (group 1); the difference was statistically significant (p<0.05). Among the group 2 students, 26% achieved a grade of A, and 37% achieved a grade of B. In contrast, only 7% of the group 1 students obtained a grade of A, and 31% achieved a grade of B. These results suggest that video triggers may offer an advantage over conventional methods and their inclusion in lectures can be a way to enhance students' learning.